2009
DOI: 10.1590/s1807-59322009000200004
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Brazilian-Portuguese Version of the Gesture Behavior Test for Patients with Non-Specific Chronic Low Back Pain

Abstract: Furtado R, Jones A, Furtado RNV, Jennings F, Natour J. Validation of the brazilian-portuguese version of the gesture behavior test for patients with non-specific chronic low back pain. Clinics. 2009;64:83-90. OBJECTIVE:To develop a Brazilian version of the gesture behavior test (GBT) for patients with chronic low back pain. METHODS: Translation of GBT into Portuguese was performed by a rheumatologist fluent in the language of origin (French) and skilled in the validation of questionnaires. This translated vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
2
10
0
4
Order By: Relevance
“…Students who sleep in the prone position have a higher prevalence of back pain. These results are in accordance with the literature 35 , where it has been reported that it is not advisable to sleep in the prone position, as this position favors increased lumbar lordosis 36 and exposes the neck to the limit of its range of motion, which can cause sprains and cervicalgia 36 . This position, when adopted as a daily postural habit, can also contribute to an anterior projection of the internal organs and stretching of the abdominal muscles 35 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Students who sleep in the prone position have a higher prevalence of back pain. These results are in accordance with the literature 35 , where it has been reported that it is not advisable to sleep in the prone position, as this position favors increased lumbar lordosis 36 and exposes the neck to the limit of its range of motion, which can cause sprains and cervicalgia 36 . This position, when adopted as a daily postural habit, can also contribute to an anterior projection of the internal organs and stretching of the abdominal muscles 35 .…”
Section: Discussionsupporting
confidence: 93%
“…This position, when adopted as a daily postural habit, can also contribute to an anterior projection of the internal organs and stretching of the abdominal muscles 35 . Thus, it is recommended that of the three most common sleeping positions (supine, lateral and prone), lateral and supine are the most appropriate positions 36 . A significant relationship was found between the occurrence of back pain and inadequate sitting posture for writing.…”
Section: Discussionmentioning
confidence: 99%
“…Good postural habits are important for proper functioning of the musculoskeletal system30 ) , and poor postural behaviors may be a risk factor for nonspecific chronic back pain16 ) and postural changes28 ) . The proper use of body mechanics, simulated in the Back School classes, allows for better adjustments of the musculoskeletal system through better balance and distribution of effort required to perform ADL, and can mitigate pain and degenerative processes31 ) ; however, this mitigation depends on complex interactions between biomechanical and neuromuscular functions30 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The calculation used a confidence level of 95%, a maximum average estimated error of 5% (6.47), and a standard deviation (1.06) of the primary variable (evaluation of dynamic posture in ADL) obtained from the literature16 ) . Thus, it was determined that a minimum of 41 subjects were required to fulfill the purposes of the present study.…”
Section: Methodsmentioning
confidence: 99%
“…5,6,27 However another approach reinforces the importance of identifying the risk factors in young people and adopting primary care, instead of only focusing on policies and treatments during adulthood and in already triggered cases. 6,13,27,30 The OLBPYQ is thus aimed at detecting the problem as soon as the patient mentions low back pain, approaching questions such as occurrence, frequency, intensity and the risk factors which, according to the literature, point in the direction of the outcome. As in other studies, the pain intensity in young people was detected through a visual analogical scale which has been considered valid and reliable.…”
Section: 13mentioning
confidence: 99%